Взаимодействие механически активированного гидрида титана с азотом и кислородом - Савяк, М.П.; Уварова, И.В.; Тимофеева, И.И.; Литвиненко, В.Ф.; Солонин, Ю.М. (Видавничий дім "Академперіодика" НАН України, 2008)
The milling of titanium hydride in a planetary mill is shown to increase the specific surface area of powder, to decrease the hydrogen content in it, and to intensify chemical activity. This makes it possible to obtain titanium nitride from the titanium hydride in a nitrogen atmosphere at as low temperature as 500 ◦C. Due to the presence of oxygen adsorbed by a mechanically activated powder under heating in a nitrogen atmosphere, the reaction of intramolecular oxidation-reduction of titanium takes place. As a result, the lower oxide Ti2O is formed.